Stereotypical Statements as Social-Psycholinguistic Phenomenon - Matevosyan, Lianna (Armenian Folia Anglistika, 2009)
The list of ready-made and fixed sentences is one of the layers of the linguistic consciousness of a man. The speaker makes the relevant choice from the existing vocabulary depending on the communicative situation. Otherwise stated, one of the components of human consciousness is the stereotypical speech behavior which is conditioned by the stereotypical situation. For instance, when meeting (stereotypical situation “meeting”) people greet (stereotype of behavior) each other with the following expressions – “hello, good afternoon”, etc. (stereotype of speech).The linguistic consciousness is multi-layered and one of its structural pillars is the stereotypical layer with a reflexive nature. Though stereotypical expressions exist in human vocabulary as ready-made sentences, it is only in certain situations that they appear in the depth of the memory and may not wake up in the consciousness of some people.The investigation of stereotypical expressions, their structural classification and distribution in accordance with communicative situations and themes is actual both in teaching and in theory.